2000
DOI: 10.1007/s004240000295
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of calcium entry and exit in quiescent rat ventricular myocytes

Abstract: The aim of this work was to obtain the first quantitative measurements of Ca2+ influx and efflux in quiescent cardiac cells. The relationship between free and total Ca2+ was obtained during a caffeine application. This buffering curve was then used to calculate changes of total Ca2+ from measurements of free cytosolic [Ca2+] ([Ca2+]i) made with Indo-1. The rate of Ca2+ removal from the cytoplasm was calculated by differentiating total Ca2+ with respect to time. The dependence of d(total Ca2+)/dt on [Ca2+]i was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
3
13
1
Order By: Relevance
“…However, the extent of inhibition was small-only 8%-and may have been below the detection limit of Takaki et al If we accept this value and that of the microcalorimetrically-measured rate of heat production of quiescent rat trabeculae presented in Table 2 (50-100 mW g dry Ϫ1 [67,68]), the cost of maintaining the resting concentration of intracellular calcium ion would be about 1-2 mW g Ϫ1 . Note that this value is of the same order (0.5 mW g Ϫ1 ) as that calculated from the data of Choi et al [174], above, and proposed as the lower limit of the metabolic cost of achieving basal Ca 2ϩ homeostasis in quiescent mammalian myocardium.…”
Section: Contributors To the Energysupporting
confidence: 78%
See 2 more Smart Citations
“…However, the extent of inhibition was small-only 8%-and may have been below the detection limit of Takaki et al If we accept this value and that of the microcalorimetrically-measured rate of heat production of quiescent rat trabeculae presented in Table 2 (50-100 mW g dry Ϫ1 [67,68]), the cost of maintaining the resting concentration of intracellular calcium ion would be about 1-2 mW g Ϫ1 . Note that this value is of the same order (0.5 mW g Ϫ1 ) as that calculated from the data of Choi et al [174], above, and proposed as the lower limit of the metabolic cost of achieving basal Ca 2ϩ homeostasis in quiescent mammalian myocardium.…”
Section: Contributors To the Energysupporting
confidence: 78%
“…The study of Choi et al [174] revealed a small contribution to resting Ca 2ϩ influx via nifedipine-sensitive (i.e., L-type) Ca 2ϩ channels. The magnitude of this component, at a whole-cell patch-clamp potential of Ϫ40 mV, amounted to about 0.8 M s Ϫ1 or about 0.08 mW g Ϫ1 .…”
Section: Contributors To the Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Block of the exchanger might alter local Ca i , thus altering Ca 2ϩ -activated currents. However, Choi et al 15 have shown that even when Ca i is increased using caffeine (ie, to levels higher than those in the present study, in which Ca i was buffered with BAPTA), no resulting current was observed in rat ventricular myocytes when the exchanger was inhibited by Ni or by the absence of bathing Na ϩ and Ca 2ϩ , making this unlikely.…”
Section: Current Measurementscontrasting
confidence: 40%
“…25 influx in rat ventricular myocytes. 30 The latter possibility is suggested by recent work indicating that during adrenergic stimulation, the calcium current can activate Ca 2ϩ entry on …”
Section: Discussionmentioning
confidence: 87%